2022
DOI: 10.1111/apce.12371
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cooperative membership on production efficiency of smallholder goat farmers in Nepal

Abstract: Goat is a source of cash income to smallholders in many developing countries. The productivity of goat farmers is poorly understood and assumed similar across all households. Cooperatives are hailed as an institution that can provide market power to smallholders in developing countries. We assess the impact of cooperatives on the technical efficiency of goat farmers in Nepal. Multistage sampling and in-person interviews were used to collect information from 334 nonmember and 327 member cooperative farmers from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 72 publications
0
30
1
Order By: Relevance
“…Prior evidence also reveals that cooperative membership plays a significant role in improving the technical efficiency of crop and livestock production. (Abate et al 2014;Addai et al 2022;Ahado et al 2021;Lin et al 2022;Neupane et al 2022;Olagunju et al 2021;Qu et al 2020). Ahado et al (2021) analyzed the impact of cooperative membership on the technical efficiency of potato farmers in Mongolia and found that cooperative members are more technically efficient with an average technical efficiency between 64% and 71%, in comparison to 54%-57% for nonmembers.…”
Section: The Mechanism Of How Cooperative Membership Affects Farm Yieldmentioning
confidence: 99%
See 4 more Smart Citations
“…Prior evidence also reveals that cooperative membership plays a significant role in improving the technical efficiency of crop and livestock production. (Abate et al 2014;Addai et al 2022;Ahado et al 2021;Lin et al 2022;Neupane et al 2022;Olagunju et al 2021;Qu et al 2020). Ahado et al (2021) analyzed the impact of cooperative membership on the technical efficiency of potato farmers in Mongolia and found that cooperative members are more technically efficient with an average technical efficiency between 64% and 71%, in comparison to 54%-57% for nonmembers.…”
Section: The Mechanism Of How Cooperative Membership Affects Farm Yieldmentioning
confidence: 99%
“…This is further confirmed by Olagunju et al (2021), who investigated maize production in Nigeria and found that the technical efficiency of cooperative members is 49% higher than that of non-members. Neupane et al (2022) estimated the production efficiency of goat production in Nepal. They found that the average technical efficiency scores of cooperative members and non-members are 93.2% and 90.7%, and the difference is statistically significant.…”
Section: The Mechanism Of How Cooperative Membership Affects Farm Yieldmentioning
confidence: 99%
See 3 more Smart Citations